THE IMPACT OF ROLE-PLAYING LEARNING MODEL ON THE EDUCATIONAL PROCESS IN MADRASAH IBTIDAIYAH: A QUALITATIVE SYSTEMATIC REVIEW - Amrulloh, Sholahuddin (PROGRES PENDIDIKAN, 2026)
Teachers often face challenges in the classroom due to their limited understanding of how to choose appropriate learning models, which leads to students not fully engaging with the learning material. The role-playing learning model offers the advantage of providing students with hands-on experience during the learning process, which can enhance their curiosity and help alleviate boredom. This study aims to evaluate the effectiveness of the role-playing learning model in elementary school education. Using the Systematic Literature Review (SLR) method, the researchers reviewed 8 articles published between 2019 and 2023. The search keyword used was "Role-Playing Learning" in the Google Scholar database. The findings, presented in a table, demonstrate that the role-playing learning model is effective in promoting student engagement. The improvements observed in various learning aspects suggest that the role-playing model enhances motivation and learning outcomes, making the learning experience more meaningful.